Insights of Ramayana on a Management Perspective - Soumyajit Palit (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Ancient Indian epic The Ramayana provides valuable insights into Dharmic Management, an idea that combines conventional dharmic principles with contemporary management techniques. In the framework of the Ramayana, Dharmic Management highlights the significance of moral principles, moral behaviour, and justice in leadership and decision-making. It promotes an approach to management that is in line with the cosmic law known as Dharma, which preserves the universe’s order. Through the activities of its protagonists, the epic depicts several aspects of management. For instance, Lord Rama is a role model for ethical leadership because of his unwavering commitment to Dharma despite suffering hardship and personal loss. The way he leads his squad to success in the fight against Ravana, treats his enemies with respect, and leads his allies shows how important ethical governance, collaboration, and strategic preparation are. The story also emphasizes how important control and attentiveness are to management. The adventures of the characters demonstrate the necessity of ongoing supervision and the capacity to adjust to shifting conditions—qualities that are critical for contemporary managers. The Ramayana teaches leadership, ethics, people management, strategy, and decision-making, all of which serve as building blocks for Dharmic Management. These teachings not only have cultural and spiritual significance, but they are also realistically applicable in today’s management situations, assisting leaders in navigating the corporate world’s difficulties with integrity and knowledge.